The neural substrates responsible for food odor processing: an activation likelihood estimation meta-analysis - Oka, Nodoka; Iwai, Koichiro; Sakai, Hiroyuki (Frontiers in Neuroscience, 2023)
In many species including humans, food odors appear to play a distinct role when compared with other odors. Despite their functional distinction, the neural substrates responsible for food odor processing remain unclear in humans. This study aimed to identify brain regions involved in food odor processing using activation likelihood estimation (ALE) meta-analysis. We selected olfactory neuroimaging studies conducted with sufficient methodological validity using pleasant odors. We then divided the studies into food and non-food odor conditions. Finally, we performed an ALE meta-analysis for each category and compared the ALE maps of the two categories to identify the neural substrates responsible for food odor processing after minimizing the confounding factor of odor pleasantness. The resultant ALE maps revealed that early olfactory areas are more extensively activated by food than non-food odors. Subsequent contrast analysis identified a cluster in the left putamen as the most likely neural substrate underlying food odor processing. In conclusion, food odor processing is characterized by the functional network involved in olfactory sensorimotor transformation for approaching behaviors to edible odors, such as active sniffing.